Impact of Agency Costs on the Relationship between Internal Control Quality and Earnings Management - Mahdi Faghani (Ph.D) (Shahid Bahonar University of Kerman, 2018)
According to the statement of Tehran Securities and Exchange Organization (SEO), reporting important weaknesses of internal controls and designing an effective system of internal control are necessary in achieving micro and macro goals of company. This study investigates the effect of agency costs on the relationship between quality of internal controls and earnings management in the listed companies in the Tehran Stock Exchange (TSE). We used the data collected from 96 companies in the TSE, during 2010-2015, with totally 672 firm-years observations, and the regression panel data model. Results showed that agency costs moderate the relationship between quality of internal controls and earnings management. And there is inverse relationship between quality of internal controls and earnings management in the absence of agency costs. This inverse relationship becomes exaggerated, when there are agency costs. This is because quality of internal controls affects earnings management of companies by reducing agency costs.